2013
DOI: 10.1371/journal.pone.0067431
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 Inhibits Breast Cancer Partially through Repressing the Hedgehog Signaling Pathway

Abstract: Constitutive activation of the Hedgehog (Hh) signaling pathway has been implicated in the development of many human malignancies. Hh targets, such as Patched (PTCH), smoothened (SMO), Sonic hedgehog (SHH) and glioma-associated oncogene homologue 1 (GLI1), are markers of Hh signaling activation and expressed in most Hh-associated tumors. The protein kinase LKB1 has been shown to slow proliferation and induce cell-cycle arrest in many cell lines. In this study, we observed that activated LKB1 decreased the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…Our results are similar to those from glioma, mammary cancer and SCCHN patients who displayed high expression level of Gli1 and poor prognosis (Zhuang et al, 2013;Xin et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Our results are similar to those from glioma, mammary cancer and SCCHN patients who displayed high expression level of Gli1 and poor prognosis (Zhuang et al, 2013;Xin et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Although many of the signaling pathways involved in breast tumors have been elucidated, others are still being discovered. After many years of speculation that polarity disruption is fundamental to cancer, recent data have confirmed that defects in the epithelial polarity machinery accelerate solid tumor progression in mammals (2)(3)(4)(5)(6). The mechanisms by which polarity restrains tumor progression remain largely unknown.…”
mentioning
confidence: 99%
“…It is worth noting that most of the pathways identified by the clusters of differentially expressed miRNAs were related to both breast cancer and more general cancer development (e.g., ErbB, mTOR, TGFb, Hedgehog, and Wnt pathways; refs. [26][27][28][29][30]. We then observed that the three miRNA clusters targeted pathways also related to metabolic and endocrine systems, such as cholesterol synthesis, steroid biosynthesis, and the insulin pathway recognized in the ORDET cohort, as well as in other studies as pathways involved in breast cancer development (27,31,32).…”
Section: Resultsmentioning
confidence: 75%